Estudio de Mercado de Productos Forestales a partir de la Factibilidad de un punto de Venta basado en el Manejo Forestal en CODEFORSA - Quesada-Montero, Jose Carlos (Instituto Tecnológico de Costa Rica, 2016)
The roundwood production has been increasing in the country in recent years (Barrantes y Ugalde, 2015), however, commerce in forest products has increasingly challenges (Navarro, G., Santamaría,O., Vargas, L., y Milla, V. 2014). The objective of this study was to make a market study to determine the feasibility of developing a point of sale of timber products from the forest management of the beneficiaries of the Committee on Forestry Development of San Carlos (CODEFORSA). In order to determine the offer was counted with active cases of PSA and other inactive, but there still have standing timber, it took into account the volume of wood extracted from the management plans and with information from PSA and PGM, were created projections from 2015 to 2020. To determine the demand, samples were taken from 50 industries with three different types of markets, it which allowed defining species and products require in the market. To determine the location of the point of sale three methods were applied. The location was analyzed to determine the possibility to establish the sales point by CODEFORSA. The study results suggest that it is feasible to establish a point of sale by CODEFORSA, however, it requires a change in the species that are being reforested. Also the economic study determined that it is more profitable if has its own sawmill to service.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2016.
Keywords: Comercialización; Diversificación; Forestal; Costos; Reforestación